Pemakaian Gaya Bahasa Sarkasme Dimedia Sosial Twitter - Susanti Marisya; Dwi Mutia Chan; Mia Afrilia (Kilau Publishing, 2025)
This study is motivated by the widespread use of sarcastic language on social media, particularly Twitter, as a form of public expression in conveying criticism, satire, and dissatisfaction toward certain events or individuals. The use of sharp and impolite sarcasm indicates a shift in language ethics in digital communication. This study aims to describe the types of sarcastic language styles found in posts and comments on the Twitter accounts @tubirfess, @AREAJULID, and @Lambe_Turah. This research employed a qualitative approach with a descriptive method. The object of this study was sarcastic language style, while the data sources consisted of posts and netizen comments from the three Twitter accounts collected from July to October 2024. The data were collected through documentation, reading, and note-taking techniques. The data were analyzed by identifying, classifying, describing, and drawing conclusions about the types of sarcasm based on Elizabeth Camp’s theory, namely propositional sarcasm, lexical sarcasm, sarcasm introduced by the word “like,” and illocutionary sarcasm. The results show that there were 74 instances of sarcasm. The most dominant type was propositional sarcasm, with 32 data, followed by illocutionary sarcasm with 22 data and lexical sarcasm with 20 data, while sarcasm introduced by the word “like” was not found. These findings imply that Twitter has become a space for critical expression that frequently employs sarcastic language, highlighting the need for more polite and responsible language awareness in digital communication.